Penerapan Pembelajaran Fun Learning Based On Scientific Approach Dalam Pembentukan Karakter Siswa Pada Mata Pelajaran Aqidah Akhlak Kelas VIII MTs Darul Ulum Hinai Kanan Kecamatan Hinai - Nurlia Sari; Usmaidar Usmaidar; Endah Retno Suci (Yayasan Rahmat Islamiyah, 2022)
The purpose of this research is to find out the application of fun learning based on scientific approach in the formation of character of class VIIIA MTs Darul Ulum Hinai Kanan Subdistrict students. The type of research used in this research is the qualitative type with a field research approach. The results showed that the application of fun learning based on scientific approach has been well implemented in MTs Darul Ulum Hinai Kanan on moral aqidah learning. The formation of student character has been done by setting an example and habituation in students for the formation of self-character in the form of behavior that reflects noble morals in every word and action both with teachers, fellow friends and parents. The application of fun learning based on scientific approach is able to shape the character of students in moral aqidah lessons where students have a character that reflects noble morals in every word and action both with teachers, fellow friends and parents. The process of learning morals given by teachers emphasizes more on students' ability to understand about the application of Islamic values in everyday life such as akhlaq to parents and teachers and love each other and respect each other's friends.